2015
DOI: 10.3758/s13423-015-0949-6
|View full text |Cite
|
Sign up to set email alerts
|

More heads choose better than one: Group decision making can eliminate probability matching

Abstract: Probability matching is a robust and common failure to adhere to normative predictions in sequential decision making. We show that this choice anomaly is nearly eradicated by gathering individual decision makers into small groups and asking the groups to decide. The group choice advantage emerged both when participants generated responses for an entire sequence of choices without outcome feedback (Exp.1a) and when participants made trial-by-trial predictions with outcome feedback after each decision (Exp.1b). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…A wide array of research in the areas of judgment and decision-making, as well as memory and reasoning, has demonstrated that the consequences of cognitive processes often thoroughly deviate from what is normatively considered to be rational behaviour. It was in the late 1990s that scholars became aware of the substantial variability across participants on each of the cognitive bias tasks (Cavojová, 2016;Schulze & Newell, 2016;Toplak et al, 2011). Thus, individual differences play a key role in the deviation between the outcomes of cognitive processes and those of normative models that have resulted in the growing body of correlational research of cognitive biases.…”
Section: Cognitive Reflection Testmentioning
confidence: 99%
“…A wide array of research in the areas of judgment and decision-making, as well as memory and reasoning, has demonstrated that the consequences of cognitive processes often thoroughly deviate from what is normatively considered to be rational behaviour. It was in the late 1990s that scholars became aware of the substantial variability across participants on each of the cognitive bias tasks (Cavojová, 2016;Schulze & Newell, 2016;Toplak et al, 2011). Thus, individual differences play a key role in the deviation between the outcomes of cognitive processes and those of normative models that have resulted in the growing body of correlational research of cognitive biases.…”
Section: Cognitive Reflection Testmentioning
confidence: 99%
“…The flexibility in how people generate representations is demonstrated both by observations that their representations of the same environment can show considerable differences (e.g., Gaissmaier & Schooler 2008;Schulze & Newell 2016), and by observations that such representations can be improved on (e.g., Szollosi et al 2019). The potential explanations that (a) these are in fact not new or improved representations, but result from the misapplication of strategies that evolved in a different evolutionary milieu; or (b) that people assess all potentially relevant features of the environment are both unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…However, real-world decision-making is a social, group-based process informed by the beliefs of others (Tranter, 2011 ). Previous research shows that groups are better able than individuals to attenuate cognitive biases and decision heuristics (Kugler et al, 2012 ; Schulze and Newell, 2016 ), as well as identify, evaluate, and resolve competing hypotheses (Trouche et al, 2015 ; Larrick, 2016 ). These benefits notwithstanding, it is important to note that groups do not outperform individuals in all tasks.…”
Section: Introductionmentioning
confidence: 99%